2013
DOI: 10.1002/jobm.201200757
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of submerged fermentation of Thelephora ganbajun zang

Abstract: The effects of the fermentation conditions on both the biomass yield and the organic selenium yield of Thelephora ganbajun zang were studied. The components most suitable for the submerged fermentation medium were examined using the orthogonal array method; they comprised sucrose at 30 g L(-1) , carbamide 1 g L(-1) , corn steep liquor 8 g L(-1) , MgSO4 ·7H2 O 0.3 g L(-1) , KH2 PO4 0.5 g L(-1) , and NaCl 5 g L(-1) . The optimum cultivation conditions that resulted in maximal biomass yield were obtained using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Thelephora ganbajun is a rare wild edible fungus that is distributed in pine forests in high-altitude areas of Yunnan Province, southwestern China [11][12][13][14][15]. In the present study, we found that T. ganbajun could accumulate zinc in the form of zinc-enriched polysaccharides.…”
Section: Introductionsupporting
confidence: 48%
“…Thelephora ganbajun is a rare wild edible fungus that is distributed in pine forests in high-altitude areas of Yunnan Province, southwestern China [11][12][13][14][15]. In the present study, we found that T. ganbajun could accumulate zinc in the form of zinc-enriched polysaccharides.…”
Section: Introductionsupporting
confidence: 48%
“…The mushroom Thelephora ganbajun , known as ‘‘Gan-Ba-Jun’’ in Chinese, is an ectomycorrhizal fungus that grows in symbiosis with pine trees in Yunnan Province of China [7,8,9]. It is a delicious and popular food for its unique flavor.…”
Section: Introductionmentioning
confidence: 99%
“…However, its production remains limited due to challenging growing conditions, its inability to be cultivated artificially, and the ecological impact of human activities. Thelephora ganbajun Zang contains amino acids, proteins, polysaccharides, vitamins, and minerals that contribute to human health [2]. A Fouriertransform infrared (FTIR) spectrometer was employed to characterize the fruiting body of T. ganbajun, and the results revealed that the primary absorption peaks represented proteins and polysaccharides, with the polysaccharides containing αand β-glycosidic bonds.…”
Section: Introductionmentioning
confidence: 99%